School Leaders' Roles in Promoting Early Childhood Health - Arifin, Zainul; Arifin, Imron; Aisyah, Eny Nur (Al-Qalam Institue, 2024)
The purpose of this study was to look at how school leaders play a role in effectively supporting early childhood health, find difficulties in incorporating health programs into educational settings, and develop methods to improve the success of health promotion. The method used is a qualitative approach, which includes interviews with school leaders from different countries and literature studies. The results show that school leadership drives change in improving early childhood health. However, there are difficulties in incorporating health programs into the curriculum. In addition, collaboration between schools and communities, increased training of school leaders, and the implementation of supportive policies are all part of a successful approach. Global and local policies must also assist school leaders in improving health in a sustainable manner. The study encourages school leaders to be more active in incorporating health programs and supporting existing policies to help early childhood health.